PERANCANGAN MEDIA VIDEO INTERIOR BERBENTUK ANIMASI DENGAN MENGGUNAKAN 3DS MAX - Wahyu Hidayat; Farhan Rachmatullah (Universitas Raharja, 2014)
Interior design and decoration for this often happens in common where they like in a the same profession. Becausethey both have the same goal, namely to provide a sense of beauty and comfort in any room. The Interior decoration is only a small part of his task an interior designer.Interior dandekorator interior designers are equally important in samamemilikiperan to improve the quality of the room, although both are different. As for the field that will be needed at a company or organization to design a media campaign in promoting and informing a product item or service to the community.So the company becomes taxable in the community and in promoting a product or a simulation of the design you want. To promote it field examples like design, Interior, Multimedia, and animations.